Pico turbines, the solution to self-supply energy to the water supply network. A case study in Las Palmas de Gran Canaria. (15th August 2021) - Borge-Diez, David; Godoy-Déniz, Juan Manuel; López-Rey, África; Colmenar-Santos, Antonio
Abstract: This paper describes the integration of the pico turbines in the drinking water network of the city of Las Palmas de Gran Canaria (Spain). World's drinking water supply companies need updates his infrastructure and technology to turn existing networks into smart water networks, to preserve people's health by ensuring the potability of water for human consumption. The essential parameters for water quality (such as chlorine level, pH, turbidity and others) can be easily measured using sensors inserted in the pipes and in the storage and distribution tanks. Access to this information in real time and immediate action is essential to ensure the health of the people who access this vital element. It is therefore essential to increase the number of sensors and the analysis of the data they provide in order to detect anomalies, correct them and anticipate their consequences. Some of the objectives are the correct measurement of meters to detect leaks and anomalous consumption, saving water and energy, avoiding water and air pollution, achieving efficient supply to the consumer and achieving profitable, efficient and environmentally sustainable urban hydraulic systems. All systems require power, the pico turbines inserted in the network can supply power without affecting the normal operation of the network. Pico turbines are highly efficient, low cost and easy to install systems, but they are not widely used. The case exposed in this city could be replicated in many urban systems, it is novel that there is no literature of massive applications, existing a wide capacity of implantation and development of this technology. When it seems that the locations for the installation of hydroelectric plants have been exhausted, it is time to commit to the development of this mature technology on the micro-scale of the infrastructures already created, the novelty is to continue discovering those places where there is untapped energy potential. There is capacity to grow in very small hydroelectric systems with immediate profitability. The researchers in this article describe the first phase of an investigation that has gone hand in hand with its validation and actual exploitation. The aim is for managers not to forget this technology, which has a very wide growth field to satisfy the small demand for distributed energy in water networks of all types. The authors hope that the results of the research carried out will motivate other technicians to apply the energy potential of their water networks for the self-sufficiency of their control, remote control, chemical dosage and water analysis systems. The applications they carry out will be immediately profitable. Graphical abstract: Image 1 Highlights: Pico turbines allow the self-sufficiency of many points of control of the Drinking Water Network. It is possible to use pico turbines to reduce the energy consumption of many installations. Network operator dissipates excess energy to prevent damage. Now is proposed how use that energy. The pico turbines technology is more than mature, but not sufficiently disclosed. This technology is cheap, very profitable and reduces CO2 emissions.